Clonal Micropropagation of Cranberry (Oxycoccus palustris Pers.) - Sergey S. Makarov; Irina B. Kuznetsova; Mikhail T. Upadyshev; Sergey A. Rodin; Anton I. Chudetsky (Техника и технология пищевых производств)
Introduction. The last decade saw a considerable increase in the demand for European cranberry planting material (Oxyccocus palustris Pers.) among consumers of non-timber forest products. Cranberry possesses high nutritional and medicinal value. Cultivars and hybrids of European cranberry prove extremely productive for plantation growth using the method of clonal micropropagation with revitalized planting material. Study objects and methods. The research featured European cranberry plants of the Dar Kostromy cultivar and its hybrid form 1-15-635. The study focused on the effect of various medications and growth regulators on the biometric profile of European cranberry and its adaptation to non-sterile conditions at all stages of in vivo clonal micropropagation. Results and discussion. During the introduction stage, the highest viability belonged to the explants treated with AgNO3 (95–96%) and Lizoformin 3000 (5%) as the main sterilizing solutions at a 10-min exposure and a 5% solution of Ecosterilizer (1:1) at a 20-min exposure (90–95%). During the micropropagation proper, the number, average length, and total growth of shoots increased as the concentration of cytokinin 2ip in the WPM 1/4 nutrient medium rose from 1.0 to 5.0 mg/L. At the stage of in vitro rooting, the maximal number, average length, and total growth of roots in regenerated plants for both cultivars were observed when Kornerost 5.0 mg/L was added to the WPM 1/4 nutrient medium. At the stage of adaptation to in vivo conditions, Micogel 0.2 mg/L contributed to the highest survival rate (94–100%). Conclusion. During clonal micropropagation in vitro, the biometric profile of European cranberry (Oxyccocus palustris Pers.) and its survival rate under non-sterile conditions in vivo proved to depend on various growth-regulating substances and their concentrations.